SAT0299 Angiogenesis Biomarkers and Doppler Ultrasound of Uterine Arteries in Patients with Systemic Lupus Erythematosus and/or Antiphospholipid Syndrome Can Be Helpful in Differential Diagnosis between Preeclampisa and Disease Activity. (15th July 2016) - Rodriguez, E.; Galindo, M.; Gonzalo-Gil, E.; Usategui, A.; Herráiz, I.; Gόmez-Arriaga, P.; Vallejo, P.; Lόpez-Jiménez, A.; Galindo, A.
Abstract : Background: Preeclampsia (PE) is a specific pregnancy syndrome that affects 2–5% of healthy women. This risk increases up to 10–30% in patients with autoimmune diseases such as Systemic Lupus Erythematosus (SLE) and/or Antiphospholipid Syndrome (APS). Differential diagnosis between PE and disease flare during pregnancy is often difficult. Pulsatility index of uterine arteries (mPI-UtA), serum levels of endoglin and the ratio tyrosine kinase-like soluble receptor/ placental growth factor (sFlt-1/PlGF) are useful markers for early diagnosis of PE, even in asymptomatic women. Objectives: To analyse the utility of these markers among pregnant patients with SLE/APS. Methods: We included patients consecutively followed in our high-risk pregnancy clinic from 2008 to the present. These patients had diagnosis of SLE (ACR criteria 1987), LES-like (<4 ACR-SLE 1987 criteria), APS (Sydney criteria) or antiphospholipid antibodies without fulfilling criteria APS (aPL). PE and its severity were diagnosed according to the International Society for the Study of Hypertension in Pregnancy criteria (ISSHP). Lupus activity was assessed with moderate considering SLEPDAI index ≥6 and APS according to the clinical activity. Follow-up visits were performed at 11–13, 22, 28 and 32 weeks and postpartum. We collected clinical data about autoimmune disease and pregnancy, treatments, toxic and cardiovascular risk factors, analytical data including endoglin and ratio and Doppler ultrasound (mPI-UtA). We performed a descriptive analysis, Chi-square or t-Student tests according to the type of variable. Odds ratio and confidence intervals were calculated by using simple logistic regression. Results: We analysed 58 pregnancies. Lupus activity during pregnancy was detected in 6 patients (10.3%), 5 with SLE and one with LES-like diagnosis. Two patients developed moderate to severe activity (SLEPDAI 25 and 12, respectively) with worsening since 24th week (33.3%). Two patients with SLE +/− APS developed PE (3.4%). We found statistically significant association between PlGF and ratio values in week 32 and development of PE [(mean 151.76±118.85 with p=0.023) and (89.62±114.70 with p=0.020), respectively)]. In addition, the values of endoglin, ratio and mPI-UtA were higher in PE than in normal pregnancy or flares since 24 week (see Table). On the other hand, there not seems to be differences in scores between patients with lupus activity and normal development of pregnancy. Conclusions: Despite the limited number of patients who develop complications in our cohort, it seems that the mPI-UtA, endoglin and ratio in patients with SLE and/or APS behaves as in the general population and may help in the differential diagnosis of preeclampsia and disease activity. Disclosure of Interest: None declared